Præventive potentialer – Populærkulturens overvejelser om overvågning - Hansen, Lone Koefoed; Gad, Christopher (Slagmark - Tidsskrift for idéhistorie, 2018)
This article uses the movie Minority Report (2002) as an entry point for discussing conceptions of surveillance technologies and their preventive capacities. The technological research project Intelligent Surveillance Systems located in Belfast shares a vision with MR: that it is possible to construct surveillance systems that are able to foresee criminal acts and thus to prevent them from happening. We argue that the movie exemplifies that technological development and popular culture share dreams, ideas and visions and that on a very basic level, popular culture informs technological development and vice versa. The article explores this relation and argues that popular culture provides analytic insight on important discussions about surveillance and the (future) capacities of technology.